Combined Effects of Different Bracket Bonding Adhesives and Different Resin Removal Methods on Enamel Discoloration: A Preliminary Study - Ozra Niknam; Milad Shamohammadi; Zeynab Ataei; Vahid Rakhshan (International Journal of Dentistry)
Introduction. This study aimed to investigate the effects of 3 orthodontic bracket adhesives and 3 resin removal methods on enamel discoloration. Methods. Ninety metal orthodontic brackets were bonded to 90 intact human premolars, using 3 adhesives (total etch composite (Transbond), self-etch composite (OptiBond), and light-curedresin-modified glass ionomer cement (RMGI, Fuji); n = 3 × 30). Each “bracket bonding” group (n = 30) was randomly divided into three subgroups of 10 specimens each, each with a different method of remnant resin removal (using only tungsten carbide burs; using tungsten carbide burs plus Sof-Lex polisher discs; using tungsten carbide burs and Stainbuster burs; n = 3 × 30). After bracket debonding and coffee staining (at 37°C for one week), the color change parameters (Δa, Δb, ΔL, and ΔE) were measured and then analyzed statistically (α = 0.05). Results. All 9 mean ΔE values were significantly greater than 3.7 and 1.0 (P values ≤0.002, t-test). The effects of composites and resin removal methods on the ΔE parameter (and their interaction) were significant (P values ≤0.008, two-way ANOVA). There were significant pairwise comparisons between total etch (Transbond) and each of the other composites (P values ≤0.008, Tukey). Nonetheless, the difference between self-etch (OptiBond) and RMGI (Fuji) was not significant (P=0.967). There were significant pairwise comparisons between the ΔE parameter of group “Bur + Stainbuster” and ΔE of each of the other methods (both P values ≤0.017). Conclusions. All 9 pairs of adhesives and resin removal techniques will cause quite visible discolorations. Still, self-etch composites or RMGI might be recommended over total etch composites. Moreover, using Stainbuster burs together with tungsten carbide burs is recommended to reduce discoloration. However, the coloration caused by each composite type can change drastically given the following adhesive removal technique used.